Spectral analysis of Ahuna Mons from Dawn mission's visible‐infrared spectrometer. Issue 1 (12th January 2017) - Zambon, F.; Raponi, A.; Tosi, F.; De Sanctis, M. C.; McFadden, L. A.; Carrozzo, F. G.; Longobardo, A.; Ciarniello, M.; Krohn, K.; Stephan, K.; Palomba, E.; Pieters, C. M.; et al.
Abstract: Ahuna Mons is the highest mountain on Ceres. A unique complex in terms of size, shape, and morphology, Ahuna is bordered by flanks of the talus around its summit. Recent work by Ruesch et al. (2016 ) based on Dawn's Framing Camera images shed light on the possible origin of Ahuna Mons. According to Ruesch et al. (2016), Ahuna Mons is formed by a volcanic process involving the ascent of cryomagma and extrusion onto the surface followed by dome development and subsequent spreading. Here we analyzed in detail the composition of Ahuna Mons, using data acquired by the visible and infrared spectrometer aboard Dawn. The spectral analysis reveals a relatively high abundance of carbonates and a nonhomogeneous variation in carbonate composition and abundance along Ahuna's flanks, associated with a lower amount of the Ceres's ubiquitous NH4 ‐phyllosilicates over a large portion of the flanks. The grain size is coarser on the flanks than in the surrounding regions, suggesting the presence of fresher material, also compatible with a larger abundance of carbonates. Thermal variations are seen in Ahuna, supporting the evidence of different compactness of the surface regolith in specific locations. Results of the spectral analysis are consistent with a possible cryovolcanic origin which exposed fresher material that slid down on the flanks. Key Points: Spectral analysis of Ahuna Mons reveals compositional variations that reflect multiple episodes of cryovolcanic extrusion on Ceres' surface Spectral parameter analysis of Ahuna Mons shows a gradient in the composition and abundance of carbonates Thermal variations observed in Ahuna Mons indicate different compactness of the surface regolith in specific locations